NEW SOURCE OF CYTOPLASMIC GENIC MALE STERILITY (CGMS) AND RESTORATION OF FERTILITY GENE IN RIDGE GOURD - D. KANNAN; ANJINEYULU KOTHAKOTA; PARDEEP KUMAR; NAGANAGOUDA PATIL (The Bioscan, 2014)
Ridge gourd [Luffa acutangula (Roxb.) L.] Male sterile (MS) mutant, regenerated through in vitro culture was crossed with five pollen parents. Four hybrids out of five were sterile (MS x CO 2, MS x Deepthi, MS x IC-92685, MS x IC-92671) and one (MS x Arka Sumeet) was found to be partially fertile. Male sterility in the sterile hybrids was stable throughout the flowering season. In partially fertile (MS x Arka Sumeet) hybrid was selfed to made F2 population. In this F2 population of the cross (MS × Arka Sumeet) exhibited a good fit to the 9:7 (fertile:sterile) modified ratio indicating the role of complementary genes. Two dominant fertility restorer genes (Rf1 and Rf2) either in homozygous dominant or heterozygous dominant condition restores the male fertility in presence of sterile cytoplasm. All the four three way crosses and seven F2 population regained fertility indicating the presence of dominant fertility restorer genes in Arka Sumeet. This is the first report of cytoplasmically controlled male sterility (CMS) in cucurbits where two dominant male fertility restorer nuclear genes with complementary gene action governed the restoration of male fertility.